2013
DOI: 10.1371/journal.pone.0055819
|View full text |Cite
|
Sign up to set email alerts
|

M tuberculosis in the Adjuvant Modulates Time of Appearance of CNS-Specific Effector T Cells in the Spleen through a Polymorphic Site of TLR2

Abstract: DC deliver information regulating trafficking of effector T cells along T-cell priming. However, the role of pathogen-derived motives in the regulation of movement of T cells has not been studied. We hereinafter report that amount of M tuberculosis in the adjuvant modulates relocation of PLP139-151 specific T cells. In the presence of a low dose of M tuberculosis in the adjuvant, T cells (detected by CDR3 BV-BJ spectratyping, the so-called “immunoscope”) mostly reach the spleen by day 28 after immunization (“l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…F1 (SJL × B6 Tlr2− ) mice have a reduced Tlr2 gene dosage, and we have previously demonstrated that the lower gene dosage of these mice did not lead to a difference of TLR2 expression ( 30 ). To assess if the reduction of the EAE severity was a function of the higher gene dosage in F1 (SJL × B6 wt ) with respect to F1 (SJL × B6 Tlr2− ) mice, we induced EAE in littermates that were either F1 (SJL × B6 Tlr2− ) mice, having one copy of functional Tlr2 of SJL origin, or F1 (SJL × B6 ts ), having two copies of functional Tlr2 of SJL origin.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…F1 (SJL × B6 Tlr2− ) mice have a reduced Tlr2 gene dosage, and we have previously demonstrated that the lower gene dosage of these mice did not lead to a difference of TLR2 expression ( 30 ). To assess if the reduction of the EAE severity was a function of the higher gene dosage in F1 (SJL × B6 wt ) with respect to F1 (SJL × B6 Tlr2− ) mice, we induced EAE in littermates that were either F1 (SJL × B6 Tlr2− ) mice, having one copy of functional Tlr2 of SJL origin, or F1 (SJL × B6 ts ), having two copies of functional Tlr2 of SJL origin.…”
Section: Resultsmentioning
confidence: 96%
“…We have previously shown that the polymorphism of Tlr2 modulates T cell trafficking ( 30 ). Here, we have shown that each isoform of Tlr2 displayed a set of distinct pro- and anti-inflammatory properties with Tlr2 82ile promoting type 1/17 polarization and the expansion of antigen-specific FoxP3 + Tregs, and Tlr2 82met blocking the expansion of Tregs and that of production of IFN-γ and IL-17A.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EAE in the SJL mouse model: to induce active EAE, we immunized female SJL (8-10 week-old) mice, purchased from Charles River, with an emulsion composed by a fragment of the proteo-lipid protein (PLP139-151, the immunodominant epitope) and complete Freund's adjuvant (CFA4X) containing 4 mg of heat-killed and dried Mycobacterium tuberculosis (strain H37Ra, ATTC 25177, and Bordetella Pertussis toxin (Sigma-Aldrich S.r.l., Milan, Italy). Immunization and treatments are described in the timetable in Figure S1a, according to the procedures described in our previous works [14][15][16][17]. Mice have been monitored daily for body weight, development of clinical signs and symptoms (CSS), and for disease remission/relapse.…”
Section: Introductionmentioning
confidence: 99%